Family Medicine’s ground principles: four pillars for defining its identity - Marco Aurelio Janaudis (O Mundo da Saúde)
McWhinney definition of Family Medicine is part of a historical perspective that goes back to the end of the Nineteenth century and the beginning of the Twentieth century. The reform of medical teaching brought undeniable benefits as regards quality. And with them some losses happened as well, as a necessary tribute. The fragmentation of medical knowledge brought the consequent fragmentation of the relationship patient-doctor. There is a close relationship, in the approach proposed by Family Medicine, between the work with patients and pupils being trained. We have thus the basic components both of the body of theoretical and methodological knowledge and of the practice of Family Medicine. On the one hand, Primary Attention to health, which implies to know patients individually, and also the community they are in. On the other, two components that come from the reflexive character in the practice of Family Medicine: medical education and the humanist attitude. The humanism in Family Medicine is a tool for facilitating professional reflection. The peculiar profile these three pillars confer to Family Medicine makes some investigators point to a fourth characteristic: education for leadership. Family doctors are leaders’ coaches, opinion makers, and always interlocutors for patients and students. The four pillars are at the same time a support and an action guide, theoretical bases that guarantee the identity of values and strategies for acting. The analysis of each one of these pillars deserves special attention for us to better understand this professional profile.